Role of Fear and disease on the Dynamics of two prey-one predator model with extended Holling type II functional response - Hawda Numan; Arkan Mustafa (Wasit Journal for Pure Sciences)
This paper deals with the studying and modeling the dynamical interaction between two prey where one of the prey species behave stronger than other, and one predator species,. The influence of fear is integrated into the development rate of vulnerable prey species owing to predation, with the spread of a SI illness among robust prey species. Here it is considered that predator both prey according to Holling type II functional response for two prey species. Then the formulation of the model is described and the boundness of solution of the system is discussed. The local stability as well as global stability for each model steady states is analyzed. Finally, with the help of MATLAB program, it is performed numerical simulations to support the evidence of our analytical results. Finally, a brief conclusion on the total work is given.